Jacobi Matrix Pair and Dual Alternative q-Charlier Polynomials - Atakishiyev, N. M.; Klimyk, A. U. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
By using two operators representable by Jacobi matrices, we introduce a family of q-orthogonal polynomials, which turn out to be dual with respect to alternative q-Charlier polynomials. A discrete orthogonality relation and the completeness property for these polynomials are established.